Enhancing kinematic accuracy of redundant wheeled mobile manipulators via adaptive motion planning. (November 2021) - Xing, Hongjun; Torabi, Ali; Ding, Liang; Gao, Haibo; Li, Weihua; Tavakoli, Mahdi
Abstract: An increasing demand for wheeled mobile manipulators (WMMs) in fields that require high precision tasks has introduced new requirements as far as their kinematic accuracy. A WMM consists of a manipulator mounted on a mobile base. This configuration usually makes the WMM a redundant robotic system. One limiting factor is that the kinematic accuracy of the mobile base is often lower than that of the manipulator because of modeling errors and disturbances such as slippage. Thus, it makes sense to distribute more of a given set of motion requirements for the entire mobile manipulator to the manipulator when possible — this is usually done using a weighting matrix that sums the mobile base motion and the manipulator motion. In this paper, considering a redundant WMM, a novel adaptive motion planning method is proposed as a secondary objective in the null space of the primary objective (improvement of the WMM's kinematic accuracy) for the WMM. Also, a tertiary objective to move the manipulator away from its singularity is proposed. This objective is activated if the secondary objective is feasible and the WMM still has remaining redundant degrees of freedom. The proposed method is implemented at the acceleration level to circumvent the discontinuity of the commanded joint velocity due to the adaptive motion planning algorithm. The advantages and effectiveness of the proposed approach are demonstrated with a traditional motion planning approach through experiments.